Shallow Structural Deformation Reveals Intraplate Seismicity Triggered by Graben Motion in the South China Littoral Fault Zone - Hu Yi; Wenhuan Zhan; Xiaodong Yang; Jian Li; Xiaochuan Wu; Jie Sun; Yantao Yao; Jiaxian Huang; Zelong Ju (Remote Sensing)
High-resolution seismic reflection profiles from the offshore segment of the Littoral Fault Zone (LFZ) near Nan’ao Island were analyzed to investigate fault activity and its potential link to the 1918 M7.3 earthquake. The data reveal a ~19 km-wide graben bounded by seaward- and landward-dipping normal faults, with fault-propagation folds and growth faults reaching the seafloor. Forward modeling of the fault-propagation fold indicates three discrete episodes of normal dip-slip displacement (~20 m per phase), separated by prolonged quiescent periods, suggesting episodic fault activity and seismic-scale strain accumulation. Despite the regional NW–SE compressional stress regime, active normal faulting is observed, implying vertical stress as the dominant driving force. A gravitational seismic model driven by upper crustal loading is proposed to explain both the fault motion and the down-draw tsunami observed during the 1918 event. These findings offer new insights into intraplate seismogenic mechanisms and associated hazards along the South China coast.